Effectiveness of a Social Media–Based, Health Literacy–Sensitive Diabetes Self‐Management Intervention: A Randomized Controlled Trial. Issue 6 (17th October 2019) - Kim, Su Hyun; Utz, Sonja
Abstract: Aims: The purpose of the study was to evaluate the effects of a social media–based, health literacy–sensitive diabetes management intervention on patient activation, self‐care behaviors, and glucose control compared to telephone‐based, health literacy–sensitive diabetes management intervention and usual care. Additionally, this study aimed to identify how patient health literacy influenced the effectiveness of health literacy–sensitive diabetes management interventions. Design: 3 (treatment condition) × 2 (health literacy level) randomized factorial trial. Methods: In total, 151 patients diagnosed with type 2 diabetes were randomly assigned to the social media–based or telephone‐based, health literacy–sensitive diabetes management interventions or the usual care control. The health literacy–sensitive diabetes management intervention consisted of an initial face‐to‐face diabetes nurse education using easy‐to‐read educational materials, the teach‐back method, and eight weekly action‐planning sessions guided with the use of social media or phone calls for each group. Findings: Patients with high health literacy at the 9‐week follow‐up showed higher levels of patient activation than those with low health literacy in the control group, but the effect of health literacy was no longer significant when patients were provided with social media–based or telephone‐based interventions. Patients who received the telephone‐based, health literacy–sensitive diabetes management intervention had a significantly higher score for self‐care behaviors than the usual care control group at 9 weeks' follow‐up. No other effects for self‐care behaviors or glycated hemoglobin were significant at follow‐up. Conclusions: The social media–based, health literacy–sensitive diabetes management intervention was effective at mitigating the disadvantages faced by people with low health literacy when attempting to improve self‐care activation. Clinical Relevance: Social media–based self‐management interventions accommodating low health literacy have the potential to help people overcome their disadvantages associated with low health literacy.